Experimental and Numerical Investigation of Car Cabin Temperature under Solar Load Condition using Phase Change Materials. Issue 1 (October 2020) - Srusti, Bhargava; Aravind, S; Yadhu, K; Aashish, V; Shyam Kumar, M.B.
Abstract: Cars kept in open have the tendency to attain temperatures far higher than the one prevailing in the surroundings. This condition is especially severe during summer months, and can cause a lot of discomfort to passengers, who re-occupy the car after parking it in the open for a while. Employing a Phase Change Material (PCM) can be a possible solution to control the car cabin temperature to a certain extent. This paper is focused on experimental and numerical study on employing a suitable PCM to control the car cabin temperature. Four different locations inside the car cabin namely roof, head, bottom and feet were selected for monitoring the temperature using temperature sensors. The effect of 90 minutes of exposure to the solar load is simulated by employing the Surface to Surface (S2S) radiation model available in ANSYS FLUENT 18.2. Experimental and numerical results conveyed the reduction in cabin average air temperature by ∼ 8°C after Placing the phase change material inside the four wheeler cabin. Comparison of Numerical and experimental results was carried out and the absolute average deviation in temperature predicted by S2S model from the experimental data is 9.93 %.